ANTIBACTERIAL POTENTIAL OF JAMU INGGU AGAINTS SOME BACTERIA CAUSING UPPER RESPIRATORY TRACT INFECTION - Nunung Sulistyani; Ardina Nugrahani (Jurnal Penelitian Saintek, 2015)
This study aims to examine the potential of jamu inggu as an alternative antibacterial herb that can be used against Staphylococcus aureus, Streptococcus pnuemoniae, S. Pyogenes, and Pseudomonas aeruginosa that is causing Upper Respiratory Infections (URI). Antibacteria activity test of jamu inggu was using the Agar diffusion method by Kirby-Bauer. To test jamu inggu antibacterial activity against Staphylococcus aureus, Streptococcus pnuemoniae, S. Pyogenes, and Pseudomonas aeruginosa, the diameter of the test bacteria growth inhibition zone was measured. The formation of a clear zone around the disc indicates that jamu inggu has chemical compounds that are antibacterial against Staphylococcus aureus,while the Pseudomonas aerugenosa, Streptococcus pyogenes, and S. pneumoniae bacteria cannot be inhibited by jamu inggu. It was indicated by no formation of a clear zone around the disc. Result shows that jamu inggu can be used as an alternative source of antibiotics against the Staphylococcus aureus.